You're a mean one, Matthew Prince - Janovsky, Timothy (Boy meets boy, 2022)
"Young, rich, and thoroughly spoiled, Matthew has no intention of being shipped off to some small town in New England to stay with his grandmother for Christmas...or to play nice with the attractive young man he meets there. Find a little "Joy to the World"? Not today, Santa. But when the two are forced to work together to make a charity gala go off without a hitch, Matthew may find the home he's been missing all along"--